Food safety lessons learned from the COVID‐19 pandemic - Lacombe, Alison (J Food Saf, 2020)
The COVID‐19 pandemic has ushered in a new era of food safety. To date, there is no evidence to suggest that consuming food is associated with COVID‐19. Nevertheless, COVID‐19's impact on food safety and security has been grave. The world is currently experiencing several supply chain issues as a direct result of extensive lockdowns and impacts on essential workers' safety. However, disruption in the food supply, while catastrophic in nature, has created opportunities for the advancement of medical science, data processing, security monitoring, foodborne pathogen detection, and food safety technology. This article will discuss the key components for food safety during the COVID‐19 pandemic. The discussion will draw from lessons learned early in the outbreak and will analyze the etiology of the disease through a food safety perspective. From there, we will discuss personal protective equipment, detection of SARS‐CoV‐2, useful surrogates to study SARS‐CoV‐2, and the expanding field of data science, from the food safety point of view. In the future, scientists can apply the knowledge to the containment of COVID‐19 and eventually to future pandemics.